2024
DOI: 10.1139/cjfr-2023-0109
|View full text |Cite
|
Sign up to set email alerts
|

Seed coatings containing capsaicin reduce seed removal in temperate woody species

Francesca Lanni,
Brian M. Connolly,
John L. Orrock
et al.

Abstract: Coating seeds in taste-averting chemical defenses (e.g., capsaicin from <i>Capsicum</i> spp.) can reduce rodent seed predation, and thus might promote plant establishment and forest regeneration. However, the efficacy of such seed coatings remains unknown for many woody plant species, and seed coatings have not been evaluated across different habitats where forest managers might seek to promote forest regeneration. We used two complementary seed-removal experiments in closed-canopy forests (Michiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has been extensively documented that small mammals avoid consuming chili peppers because they perceive the capsaicin (Pearson et al 2019;Lanni et al 2024); however, some rodents can consume chili peppers with lower capsaicin content (Tewksbury & Nabhan 2001). In this study, we recorded only one individual of the marsupial common opossum consuming the less pungent fruits of C. annuum (compared to C. pubescens) 7 days after exposure to the chilies in the feeding trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been extensively documented that small mammals avoid consuming chili peppers because they perceive the capsaicin (Pearson et al 2019;Lanni et al 2024); however, some rodents can consume chili peppers with lower capsaicin content (Tewksbury & Nabhan 2001). In this study, we recorded only one individual of the marsupial common opossum consuming the less pungent fruits of C. annuum (compared to C. pubescens) 7 days after exposure to the chilies in the feeding trials.…”
Section: Discussionmentioning
confidence: 99%
“…Seed coating with capsaicin is another strategy against seed predation (Tewksbury & Nabhan 2001;Lanni et al 2024). Pearson et al (2019) reported, under laboratory conditions, that deer mice (Peromyscus maniculatus) consumed fewer pepper-coated small seeds (0.0002-0.0098 g) compared to control treatments.…”
Section: Introductionmentioning
confidence: 99%